2012
DOI: 10.1111/j.1469-8986.2012.01488.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermotherapy to the facial region in and around the eyelids altered prefrontal hemodynamic responses and autonomic nervous activity during mental arithmetic

Abstract: To investigate neural mechanisms of local thermotherapy to reduce mental stress, participants were required to perform mental arithmetic after treatment by a heat- and steam-generating sheet on the facial eyelid region while hemodynamic activity and ECGs were monitored. The results indicated that thermotherapy decreased hemodynamic activity in the anterior dorsomedial prefrontal cortex (aDMPFC) involved in sympathetic activity. Consistently, thermotherapy increased parasympathetic activity while it decreased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 126 publications
1
19
0
Order By: Relevance
“…In addition, the HRV parameter returned to baseline values after the stress was over (unpublished results, Table). These results were in accordance with the studies which found a cardiac-linked parasympathetic decrease indexed by reduced RSA magnitude to cognitive stress indicating physiological adaptive response system31578182.…”
Section: Respiratory Sinus Arrhythmia (Rsa) In Response To the Acute supporting
confidence: 93%
“…In addition, the HRV parameter returned to baseline values after the stress was over (unpublished results, Table). These results were in accordance with the studies which found a cardiac-linked parasympathetic decrease indexed by reduced RSA magnitude to cognitive stress indicating physiological adaptive response system31578182.…”
Section: Respiratory Sinus Arrhythmia (Rsa) In Response To the Acute supporting
confidence: 93%
“…In the present study, favorable effects of periocular warming on feelings of restfulness and being refreshed were greater in the participants who preferred periocular warming to use of the sham mask. Many studies have shown that appropriate skin temperature manipulation [ 10 , 16 , 17 ], mainly warming, of various parts of the skin in humans can elicit a feeling of comfort and/or relaxation. A study using heart rate variability analysis has indicated that such favorable effects of periocular warming are attributable to acute activation of the parasympathetic nervous system [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the hemodynamic responses occurred faster in Ch 5 than in Ch 1, suggesting that hemodynamic responses in the aDMPFC occurred faster than those in the scalp. The aDMPFC, including the anterior cingulate cortex, has been implicated in control of various physiological responses including blood adrenocorticotropic hormone (ATCH) levels (Liberzon et al, 2007), the skin conductance response reflecting sympathetic activity (Critchley et al, 2000), and sympathetic activity (Yasui et al, 2010; Takamoto et al, 2013). Furthermore, an event-related fMRI study reported that activity of the aDMPFC preceded autonomic responses, suggesting that the aDMPFC is involved in generation of autonomic responses (Critchley et al, 2000).…”
Section: Discussionmentioning
confidence: 99%